(untitled) (Ukrainian Journal of Ophthalmology, 2026)
The paper presents the results of the study of tear production in patients with the most severe form of the dry eye syndrome - cicatricial xerosis of the eye, depending on the size of the formed symblepharons including both before and after their elimination. It was found that the removal of the eyelid scar adhesions with the eyeball by transplanting mucous lips does not improve tear production and prevents its progression. A comprehensive treatment with application of anti-inflammatory, dedystrophic, preparations stimulating regeneration and antioxidant drugs tear substituting drugs slightly improves visual acuity of such eyes. The application of obturators or diathermocoagulation of the lacrimal points slightly improves hydration of the eye. It is shown that the only possible method of vision restoration of patients with cicatricial xerosis of the eye is keratoprosthesis with a preliminary consolidation of the cornea of the mucous lips.